2016
DOI: 10.1002/acr.22842
|View full text |Cite
|
Sign up to set email alerts
|

Is Tibiofemoral or Patellofemoral Alignment or Trochlear Morphology Associated With Patellofemoral Osteoarthritis? A Systematic Review

Abstract: There is strong evidence that PFOA is associated with both trochlear morphology and frontal plane knee alignment, while evidence is limited but consistent in the sagittal and axial planes. These findings suggest that alignment should be evaluated clinically in individuals with PFOA. Clinical interventions targeting knee alignment warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 46 publications
4
63
0
2
Order By: Relevance
“…Trochlear morphology and patellofemoral alignment are associated with patellofemoral OA 12 . In the axial plane, a shallower/wider trochlea and a patella that is more laterally displaced or tilted are associated with more severe patellofemoral OA features 12 , and trochlear morphology is associated with patellofemoral alignment 13, 14 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Trochlear morphology and patellofemoral alignment are associated with patellofemoral OA 12 . In the axial plane, a shallower/wider trochlea and a patella that is more laterally displaced or tilted are associated with more severe patellofemoral OA features 12 , and trochlear morphology is associated with patellofemoral alignment 13, 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In the axial plane, a shallower/wider trochlea and a patella that is more laterally displaced or tilted are associated with more severe patellofemoral OA features 12 , and trochlear morphology is associated with patellofemoral alignment 13, 14 . Theoretically, trochlear dysplasia may cause patellar instability and result in malalignment and/or aberrant movement patterns at the patellofemoral joint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the Q angle increases the lateral force on the patella 7,14,16. It has been shown that larger Q angles are associated with femoropatellar instability and with PFOA 14,15. However, the use of the Q angle to predict PFP is controversial.…”
Section: Pfp Pathophysiology or Pathomechanicsmentioning
confidence: 99%
“…In some clinical and research settings, magnetic resonance imaging (MRI) is used to evaluate knee alignment in patellofemoral osteoarthritis (OA) and related conditions (patellofemoral pain or instability) . The advantages of MRI include lack of ionizing radiation and versatility of sequence parameters.…”
mentioning
confidence: 99%